1998
DOI: 10.1007/s004670050453
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular function in β-thalassemia

Abstract: Studies of the renal involvement in thalassemic syndromes have been varied and few. This study was designed to define the renal abnormalities associated with beta-thalassemia and to correlate the renal findings with clinical parameters. One hundred and four beta-thalassemic children with various disease severity were studied. The patients were divided into three groups: 48 with severe anemia [hematocrit (Hct) < 25%], 31 on a hypertransfusion program and desferrioxamine treatment, and 25 with moderate anemia (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
76
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 15 publications
10
76
2
1
Order By: Relevance
“…1 Although major system dysfunctions, including cardiopulmonary and reticuloendothelial systems, have been reported in patients with TM, little information is available on renal involvement. 4 In recent years, some studies have investigated renal proximal tubular damage using biomarkers including b2 microglobulin, N-acetyl-D-glucosaminidase (NAG), proteinuria, and aminoaciduria in thalassemia patients. 5,6 Moreover, a number of studies showed that patients with TM had increased urinary excretion of calcium, phosphate, magnesium, and uric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although major system dysfunctions, including cardiopulmonary and reticuloendothelial systems, have been reported in patients with TM, little information is available on renal involvement. 4 In recent years, some studies have investigated renal proximal tubular damage using biomarkers including b2 microglobulin, N-acetyl-D-glucosaminidase (NAG), proteinuria, and aminoaciduria in thalassemia patients. 5,6 Moreover, a number of studies showed that patients with TM had increased urinary excretion of calcium, phosphate, magnesium, and uric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of higher ratios of U Protein/Cr in patients is in accordance with these prior reports. 4,5,22,23 This proteinuria might be explained primarily by the impairment of proximal tubular reabsorption, which may be due to severe iron overload in the tissues where it also stimulates the production of reactive oxygen radicals and results in cellular injury. 24 As urinary protein/Cr ratio is 0.13 in our study, this degree of proteinuria is consistent with proximal tubular injury.…”
mentioning
confidence: 99%
“…(6,10) Furthermore, serum creatinine is notoriously unreliable as a marker of kidney function, and previous studies have reported normal creatinine levels in bthalassemia major patients with early tubular and glomerular dysfunction. (8,9,11,12) Our patient had evidence of proximal tubular dysfunction on deferasirox with generalized aminoaciduria, glycosuria, detection of urine protein, and elevated urine b2-microglobulin levels. Furthermore, cessation of deferasirox was followed by normalization of urinary amino acid, protein, and glucose excretion.…”
Section: Discussionmentioning
confidence: 73%
“…(6)(7)(8) The underlying cause for renal abnormalities is controversial but has been associated with chronic hypoxia related to anemia, (8,9) oxidative stress (9,10) and DFO. (6,10) Furthermore, serum creatinine is notoriously unreliable as a marker of kidney function, and previous studies have reported normal creatinine levels in bthalassemia major patients with early tubular and glomerular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…8 An association between an immunodeficiency and Fanconi syndrome has not been reported, though there are a few reports of renal tubular defects associated with hemoglobinopathies. 9,10 The pathogenesis of tubular dysfunction described in patients with ␤-thalassemia/HbE disease 9,10 may also apply to other anemic states. In various forms of thalassemia shortened red cell life span, rapid iron turnover and tissue deposition of excess iron are contributing factors to functional and physiological abnormalities.…”
Section: Discussionmentioning
confidence: 99%